(U)pravni značaj pisnega strokovnega navodila za odbiranje arhivskega gradiva iz dokumentarnega gradiva - Čibej, Nada (Javna uprava, 2022)
The issuance of written professional instructions for the selection of archives from documents, additional written professional instructions, professional and technical instructions as part of written professional instructions is an archives legal obligation. The instructions set out the duties of entities governed by public law who are subject to sanctions (penalties) in the event of non-compliance. However, the law dealing with archives does not stipulate the legal nature of written professional instructions. The legally open question remains whether written professional instructions are a material act as understood by the archive profession, a general legal act as understood by the Legislative and Legal Service of the National Assembly (the parliament), public contract or a specific administrative act. In addition, the instruction issued by the archive is also considered in the context of the criteria for the appraisal of archival material namely »needs for permanent legal value for enforcing personal rights«, determined by law. The article compares historical role and development of the written professional instruction and with systematic methodologic analysis the requirements of the legislation, which indicate that the written professional instruction have an elements of specific administrative act.
Keywords: administrative act; archives; arhivistika; arhivsko gradivo; javno pooblastilo; pisno strokovno navodilo; public authorisation; upravni akti; written professional instruction